Synthesis and Preliminary Antibacterial Activities of New 2, 3-Disubstituted-1, 3-Oxazepane-4, 7-Diones of Benzothiazole - Zeid Hassan Abood (Journal of Global Pharma Technology, 2020)
2-aminobenzothiazole 1 was converted to analogues diazonium salt which reacted with alkaline solution of 2-hydroxybenzaldehyde to yield azo-benzothiazole derivative 2 bearing aldehyde group. The resulting aldehyde 2 was then condensed with some aromatic amines including (4-nitroaniline, 3-nitroaniline, 4-aminophenol, 4-methoxyaniline, 4-bromoaniline, 4-chloroaniline and 2, 4-dichloroaniline) using microwave irradiation technique in absolute ethanol to produce seven imine derivatives of benzothiazole 3a-g, respectively. Treatment of the resulting imines 3a-g with succinic anhydride using microwave irradiation in dry benzene afforded seven new 1, 3-oxazepane-4, 7-diones 4a-g bearing the benzothiazole moiety, respectively. Preliminary in vitro antibacterial activity of the target compounds were investigated using two types of bacteria, Staphylococcus aurous (Gram-positive) and Escherichia coli (Gram-negative). The results indicated that all oxazepane compounds exhibited better activity to gentamycin against Gram-positive bacteria. On the other hand, the oxazepane compounds (4a, 4e and 4g) showed greater activity against Gram-negative bacteria when compared with that of the control drug.Keywords: Benzothiazoles; Oxazepanes; Imines; Azo; Antibacterial activity.